Clockwork lives - Anderson, Kevin J., 1962-; Peart, Neil (ECW Press, 2015)
Marinda Peake is a woman with a quiet, perfect life in a small village; she long ago gave up on her dreams and ambitions to take care of her ailing father, an alchemist and an inventor. When he dies, he gives Marinda a mysterious inheritance: a blank book that she must fill with other people's stories -- and ultimately her own.